QTL analysis for grain iron and zinc concentrations in two O. nivara derived backcross populations - Swamy, B.P.M.; Kaladhar, K.; Anuradha, K.; Batchu, Anil K.; Longvah, T.; Sarla, N. (Elsevier, 2018)
Identification of quantitative trait loci (QTLs) for grain mineral elements can assist in faster and more precise development of micronutrient dense rice varieties through marker-assisted breeding. In the present study, QTLs were mapped for Fe and Zn concentrations in two BC2F3 mapping populations derived from the crosses of O. sativa cv Swarna with two different accessions of O. nivara. In all, 10 and 8 QTLs were identified for grain Fe and Zn concentrations in population 1, and 7 and 5 QTLs were identified in population 2, respectively. Eighty percent of the QTLs detected in both populations were derived from O. nivara. Five QTLs for Fe and three QTLs for Zn explained more than 15% phenotypic variance either in interval or composite interval mapping. The locations of O. nivara derived QTLs such as qFe2.1, qFe3.1, qFe8.2 and qZn12.1 were consistently identified in both the populations. Epistatic interaction was observed only between RM106 and RM6 on chromosome 2 and between RM22 and RM7 on chromosome 3 for Fe concentration in population 1. Sixteen candidate genes for metal homeostasis were found to co-locate with 10 QTLs for Fe and Zn concentrations in both the populations. Most of the Fe and Zn QTLs were found to co-locate with QTLs for grain yield and grain quality traits. Some of the major effect QTLs identified can be used to improve rice grain Fe and Zn concentrations.